El deteriorament del marc normatiu de les competències lingüístiques del personal sanitari a les Illes Balears. Els seus efectes sobre el règim tuïtiu de la llengua catalana - Ballester Cardell, Maria (Revista de Llengua i Dret, 2025)
Gairebé a punt de complir-se el quarantè aniversari de l’aprovació de la Llei 3/1986, de 29 d’abril, de normalització lingüística de les Illes Balears, continua molt viu el debat sobre el règim de capacitació lingüística del personal sanitari del Servei de Salut. Les successives revisions normatives sobre l’ús de les llengües oficials en aquest àmbit i la resposta judicial, tant respecte a l’establiment del requisit de coneixements de llengua catalana com a l’adopció de mesures potencialment regressives, són una mostra de les dificultats que comporta avançar cap a un marc jurídic estable que garanteixi adequadament els drets lingüístics dels usuaris en l’àmbit assistencial i sanitari. En aquest estudi s’analitzen les tensions provocades per les fluctuacions normatives que s’han produït en les darreres legislatures i la doctrina recent del Tribunal Constitucional en relació amb la rebaixa de les competències lingüístiques del personal sanitari del Servei de Salut de les Illes Balears. Aquestes circumstàncies, en conjunt, marquen una tendència regressiva i fan minvar el nivell de protecció de la llengua catalana a les Illes Balears. , Almost on the eve of the 40th anniversary of the approval of Law 3/1986, of 29 April, on the linguistic normalisation of the Balearic Islands, the debate on the language training regime for health service staff is still very much alive. The successive regulatory revisions on the use of the official languages in this field and the judicial response, with regard to both the requirement to know Catalan and the adoption of potentially regressive measures, are an example of the difficulties involved in moving toward a stable legal framework that adequately guarantees users’ language rights in the healthcare field. This study analyses the tensions caused by the regulatory fluctuations that have occurred in recent legislatures and the recent doctrine of the Constitutional Court in relation to the reduction in the level of language competence required by healthcare staff in the Balearic Islands Health Service. These circumstances, taken together, mark a regressive trend and lower the level of protection of the Catalan language in the Balearic Islands. , Casi a punto de cumplirse el cuadragésimo aniversario de la aprobación de la Ley 3/1986, de 29 de abril, de Normalización Lingüística de las Islas Baleares, continúa muy vivo el debate sobre el régimen de capacitación lingüística del personal sanitario del Servicio de Salud. Las sucesivas revisiones normativas sobre el uso de las lenguas oficiales en este ámbito y la respuesta judicial, tanto con respecto al establecimiento del requisito de conocimientos de lengua catalana como a la adopción de medidas potencialmente regresivas, son una muestra de las dificultades que comporta avanzar hacia un marco jurídico estable que garantice adecuadamente los derechos lingüísticos de los usuarios en el ámbito asistencial y sanitario. En este estudio se analizan las tensiones provocadas por las fluctuaciones normativas que se han producido en las últimas legislaturas y la reciente doctrina del Tribunal Constitucional en relación con la rebaja de las competencias lingüísticas del personal sanitario del Servicio de Salud de las Islas Baleares. Estas circunstancias, en conjunto, marcan una tendencia regresiva y disminuyen el nivel de protección de la lengua catalana en las Islas Baleares.

The debate on staff language competences and the use of official languages in the Balearic Islands health system - Ballester Cardell, Maria; Marí Mayans, Isidor (Linguistic Minorities and Society, 2021)
The Spanish Constitution of 1978 and the Statute of Autonomy of the Balearic Islands of 1983 established the official nature of both Spanish and Catalan and entrusted public authorities with guaranteeing the right of citizens to use one or the other on an equal footing. Subsequent to the language legislation of 1986, the legal framework of Catalan has varied depending on the majority party that forms a government. The debate stirred up by these regulations demonstrates the difficulties in ensuring real equality between official languages, when social initiatives cannot translate into sufficient political support and the national political context is hostile. The article explores this debate and discusses recent regulations surrounding the official languages competencies of health system staff, from the direct experience of the authors, as members of two consultative institutions on legal and sociolinguistic matters. Keywords: language rights, official language, language competence, medical communication, health services

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Évaluation de la validité des preuves présentées dans l’étude intitulée "Language Barriers in Health Care Settings: An Annotated Bibliography of the Research Literature" - Bureau d'appui aux communautés de langue officielle (Santé Canda, 2008)

Autonomie, vitalité et identité des communautés en situation minoritaire : proposition d’un cadre conceptuel - Forgues, Éric (Revue internationale d’études canadiennes, 2010)
Quels facteurs contribuent à la vitalité linguistique d’une communauté en situation minoritaire et lui assurent les conditions propres à favoriser sa reproduction linguistique et culturelle? Nous nous proposons de présenter un modèle conceptuel susceptible de répondre à cette question. Selon ce modèle, trois facteurs sont au fondement de la reproduction linguistique d’une communauté en situation minoritaire : la gouvernance, l’identité et la vitalité, avec comme point pivot, la société civile et l’espace public. Cet article présente non seulement la fonction de ces facteurs au sein des communautés, mais les sous-fonctions qui découlent de leurs interrelations, tels que la lutte pour la reconnaissance, le droit, la complétude institutionnelle, l’engagement social et l’expression identitaire publique et privée. Ce modèle peut être utile pour saisir, d’un point de vue global, les composantes de la reproduction des communautés en situation minoritaire, pour déterminer celles qui la compromettent et, ainsi, envisager des pistes d’action.

Language-based welfare services in times of structural change: An examination of Finland’s social and healthcare reform (2023) - Himmelroos, Staffan; Sjöblom, Stefan; Vento, Isak (Revista de Llengua i Dret, 2025)
This study examines the impact of Finland’s social and healthcare reform on language-based welfare services for the Swedish-speaking population of Finland. The reform shifted healthcare responsibility from municipalities to regional wellbeing service counties (WBSCs), altering established linguistic boundaries in the process. Traditionally, municipalities have ensured the provision of services in both Finnish and Swedish in bilingual areas. Post-reform, Swedish speakers that represent a majority or substantial minority within a municipality have become a small minority within larger WBSCs, some of which include unilingual areas that lack experience in providing bilingual services. Analysis of survey data indicates that Swedish speakers in majority Swedish-speaking municipalities are the most satisfied with language services, while those in minority areas are significantly less satisfied. Notwithstanding, satisfaction among Swedish speakers in majority areas has declined significantly since the reform. The study highlights the challenges of maintaining language rights within a universal healthcare system amid structural changes and emphasises the importance of addressing linguistic needs in a state with two national languages. , Aquest estudi analitza l’impacte de la reforma social i sanitària en els serveis socials i de salut basats en la llengua per a la població de parla sueca de Finlàndia. La reforma va traslladar la responsabilitat sanitària dels municipis als serveis regionals de benestar (wellbeing service counties o WBSC), alterant així les fronteres lingüístiques establertes. Tradicionalment, els municipis havien garantit la prestació de serveis tant en finès com en suec a les zones bilingües. Després de la reforma, els parlants de suec que constituïen una majoria o una minoria important dins d’un municipi han passat a ser una petita minoria dins de WBSC més grans, alguns dels quals inclouen àrees unilingües sense experiència en la prestació de serveis bilingües. L’anàlisi de dades provinents d’enquestes indica que els parlants de suec dels municipis de majoria suecoparlant són els més satisfets amb els serveis lingüístics, mentre que els de les àrees on són minoria es mostren significativament menys satisfets. Tanmateix, la satisfacció entre els parlants de suec a les àrees on són majoria ha disminuït notablement des de la reforma. L’estudi destaca els reptes que suposa mantenir els drets lingüístics dins d’un sistema de salut universal enmig de canvis estructurals i posa èmfasi en la importància d’atendre les necessitats lingüístiques en un estat amb dues llengües nacionals. , Este estudio analiza el impacto de la reforma social y sanitaria en los servicios sociales y de salud basados en la lengua para la población de habla sueca de Finlandia. La reforma trasladó la responsabilidad sanitaria de los municipios a los servicios regionales de bienestar (wellbeing service counties o WBSC), alterando así las fronteras lingüísticas establecidas. Tradicionalmente, los municipios habían garantizado la prestación de servicios tanto en finés como en sueco en las zonas bilingües. Después de la reforma, los hablantes de sueco que constituían una mayoría o una minoría importante dentro de un municipio han pasado a ser una pequeña minoría dentro de WBSC mayores, algunos de los cuales incluyen áreas unilingües sin experiencia en la prestación de servicios bilingües. El análisis de datos provenientes de encuestas indica que los hablantes de sueco de los municipios de mayoría suecohablante son los más satisfechos con los servicios lingüísticos, mientras que los de las áreas donde son minoría se muestran significativamente menos satisfechos. Sin embargo, la satisfacción entre los hablantes de sueco en las áreas donde son mayoría ha disminuido notablemente desde la reforma. El estudio destaca los retos que supone mantener los derechos lingüísticos dentro de un sistema de salud universal en medio de cambios estructurales y pone énfasis en la importancia de atender a las necesidades lingüísticas en un estado con dos lenguas nacionales.

Welfare services from a minority perspective. Explaining satisfaction with language-based welfare services among Swedish-speaking Finns - Himmelroos, Staffan; Vento, Isak; von Schoultz, Åsa (Linguistic Minorities and Society, 2021)

Perceived importance of native language use in service encounters - Holmqvist, Jonas; Van Vaerenbergh, Yves (The Service Industries Journal, 2013)
Despite the importance of interactions in services, the role language plays in services is an under-researched field. This paper outlines for which services language is especially important. Consistent across studies in three countries (Belgium, Canada and Finland), the findings suggest that bilingual consumers find it particularly important to be served in their native language in high-involvement services. Moreover, for high-involvement services, all consumers find it important to be served in their native language. For low-involvement services, elderly consumers are less willing to switch language than young consumers. The importance of native language use did not differ between males and females.

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Bilingualism in the health system: The Catalan case - Ibáñez Ferreté, Òscar-Adrià; Mestres i Farré, Neus (Linguistic Minorities and Society, 2021)
Catalan-speaking citizens living in Catalonia have full, formal rights to use their language with all of their region’s administrations. Nevertheless, the available information on the knowledge and use of Catalan by civil servants shows that health care is a weak spot for regional administrations, due to the difficulty in covering all medical specialties. Plataforma per la Llengua has undertaken research in the form of a survey with a sample of 1,600 Catalan inhabitants, to ascertain the level of satisfaction with the enforcement of linguistic rights in public health and determine the scope of a potential language promotion policy that would have health care staff initiate conversations in Catalan. Results of government surveys suggest that language use (by both patients and providers) in the health care system, compared with language use in other areas of public administration, demonstrates the limits of the current regional language promotion policies in Catalonia. Keywords: catalan, linguistic minorities, linguistic rights, health and social services, language competencies

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Évaluation des besoins de santé et intégration à la culture francophone, anglophone et autochtone chez les enfants métis en milieu minoritaire - LeBlanc, Angèle; Roy-Charland, Annie; Paquette, Tara; Boulard Poirier, Jessica; Young, Nancy. L. (Enfance en difficulté, 2021)
Ce projet a pour objectif d’adapter et de traduire un questionnaire lié à la santé et au bien-être des enfants métis : la Mesure de la santé et du bien-être des enfants métis (MSBEM), en plus de déterminer si les enfants métis de la communauté du Grand Sudbury sont davantage intégrés à la culture autochtone, francophone ou anglophone. Mots-clés : Métis, intégration culturelle, minorité, besoins de santé, autorapport

Language and culture in the caregiving of people with dementia in care homes - What are the implications for well-being? A scoping review with a Welsh perspective - Martin, Conor; Woods, Bob; Williams, Siôn (Journal of Cross-Cultural Gerontology, 2019)
The loss of language skills is one of the most challenging aspects of living with dementia. This is particularly true for bilingual individuals, who have difficulty in maintaining fluency in more than one language. Language and culture overlap greatly, with potential implications for the well-being of people with dementia (PWD) being cared for in their ‘second’ language or culture. Our aim was to review the available relevant literature, together with an examination of the potential effects of linguistic incongruity on healthcare in general for Welsh speakers in Wales. A literature search yielded 50 articles, which were analysed using the scoping review methodological framework. We found that the presence of cultural and linguistic congruity was beneficial for PWD living in care homes, and that their absence was detrimental. The absence of linguistic congruity is a strong predictor for decreased well-being in people in such settings, due to communication barriers between residents and carers, which result mainly from the loss of PWD’s second language skills. Such barriers may lead to inappropriate care, e.g. being unable to obtain help to self-care, as well as social isolation. This review suggests that strategies need to be developed across the world to accommodate bilingual individuals requiring a care home for their dementia needs. There is a particular dearth of research regarding the influence of bilingualism on the experience of dementia care in those areas of the UK where the indigenous population are most likely to be bilingual (i.e. parts of Wales).

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

Being small and outnumbered: Service and sociocultural exclusion among older linguistic minorities in Finland - Nyqvist, Fredica; Björklund, Siv; Lindell, Marina; Nygård, Mikael (Linguistic Minorities and Society, 2021)
Our study aims to analyze the social exclusion of older Swedish and Finnish speakers living as linguistic minorities in bilingual municipalities in Finland, where municipal authorities are required to offer services in both languages. Data was taken from the 2016 Language Barometer Survey, measuring the quality of language services in bilingual municipalities (n=33). For the purposes of our study, we focused on 2,030 people between the ages of 60 and 84. We included four different language groups, unilingual Swedish and Finnish speakers and Finnish-Swedish bilinguals and examined two social exclusion domains: service and sociocultural exclusion. The results showed that living as a regional minority poses a greater challenge when it comes to social inclusion for the unilingual and bilingual Swedish minority, as opposed to the Finnish-speaking minority. We conclude that linguistic rights seem to be achieved in the most egalitarian way in bilingual municipalities where Swedish is the majority language. Keywords: older adults, linguistic minority, bilingual, social exclusion, Finland

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

L’atenció sanitària amb discordança lingüística: un estat de la qüestió des de i per a la catalanofonia - Pena Tarradelles, Joana (Revista de Llengua i Dret, 2025)
Aquest article fa una revisió bibliogràfica d’un centenar d’estudis sobre l’atenció sanitària amb discordança lingüística (ASDiL) i les conseqüències que pot tenir per als grups lingüístics minoritaris (GLMinoritaris) i minoritzats (GLMinoritzats) que l’experimenten. A diferència d’altres revisions, centrades sobretot en els GLMinoritaris d’origen migrant amb poc coneixement de la llengua d’atenció sanitària, aquest treball proposa una classificació de la bibliografia basada en dos eixos: 1) l’estatus de la llengua pròpia del grup lingüístic analitzat en cada treball i 2) el grau de coneixement per part del grup lingüístic de la llengua de comunicació sanitària. D’aquesta manera, es distingeix entre GLMinoritaris d’origen migrant no bilingüitzats, GLMinoritzats autòctons semibilingüitzats i GLMinoritzats autòctons altament bilingüitzats. Els resultats demostren que l’ASDiL pot afectar tots aquests grups, si bé amb diferències: en els GLMinoritzats autòctons semibilingüitzats i altament bilingüitzats es mantenen, amb matisos, algunes de les afectacions comunicatives detectades en els GLMinoritaris d’origen migrant, però n’emergeixen d’altres de caire més identitari. Així, l’article aporta dades rellevants per al debat actual en la catalanofonia sobre els requisits lingüístics en l’àmbit sanitari. , This article provides a literature review of around one hundred studies examining language-discordant care (ASDiL) and the consequences for those minority language groups (GLMinoritaris) and minoritised language groups (GLMinoritzats) that experience it. Unlike other reviews, which focus primarily on GLMinoritaris of migrant origin with little understanding of the language used in the clinical encounter, this work puts forward a classification of the literature based on two criteria: 1) the status of the own language (llengua pròpia) of the language group studied in each case, and 2) the group’s level of understanding of the language used in the clinical encounter. Accordingly, it distinguishes between non-bilingualised GLMinoritaris of migrant origin, semi-bilingualised autochthonous GLMinoritzats, and highly bilingualised autochthonous GLMinoritzats. The results show that ASDiL can affect all these groups, albeit with differences. The semi- and highly bilingualised GLMinoritzats are affected – though with certain nuances – by some of the communicative issues observed in the GLMinoritaris of migrant origin, but additional, more identity-related issues also emerge. The article thus provides relevant data to fuel the current debate in Catalan-speaking territories on language requirements in the healthcare sector. , Este artículo hace una revisión bibliográfica de un centenar de estudios sobre la atención sanitaria con discordancia lingüística (ASDiL) y las consecuencias que puede tener para los grupos lingüísticos minoritarios (GLMinoritarios) y minorizados (GLMinorizados) que la experimentan. A diferencia de otras revisiones, centradas sobre todo en los GLMinoritarios de origen migrante con poco conocimiento de la lengua de atención sanitaria, este trabajo propone una clasificación de la bibliografía basada en dos ejes: 1) el estatus de la lengua propia del grupo lingüístico analizado en cada trabajo y 2) el grado de conocimiento por parte del grupo lingüístico de la lengua de comunicación sanitaria. De esa manera, se distingue entre GLMinoritarios de origen migrante no bilingüizados, GLMinorizados autóctonos semibilingüizados y GLMinorizados autóctonos altamente bilingüizados. Los resultados demuestran que la ASDiL puede afectar a todos estos grupos, si bien con diferencias: en los GLMinorizados autóctonos semibilingüizados y altamente bilingüizados se mantienen, con matices, algunas de las afectaciones comunicativas detectadas en los GLMinoritarios de origen migrante, pero emergen otras de aspecto más identitario. Así, el artículo aporta datos relevantes para el debate actual en la catalanofonía sobre los requisitos lingüísticos en el ámbito sanitario.

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Navigating the meso-level bottleneck: Language rights implementation in Welsh healthcare - Prys, Cynog; Hodges, Rhian (Revista de Llengua i Dret, 2025)
Language is a key factor in the delivery of effective healthcare, especially in settings where service users speak a minoritised language. In Wales, the Welsh Government has acknowledged the importance of linguistic inclusion through initiatives such as the More than just words strategy, which aims to embed the Welsh language into health and social care services. The introduction of The Welsh Language Standards (No. 7) Regulations in 2018 marked a significant statutory development, placing legal obligations on health boards to provide services in Welsh. Despite these policy-level advancements, the integration of Welsh language services within healthcare remains uneven. Reports have highlighted persistent gaps and inconsistencies in Welsh language service provision, raising concerns about the practical challenges of implementation and its impact on service users. In this paper, we examine the structural and operational barriers encountered by meso-level actors – particularly local health boards – responsible for implementing national language policy in everyday service delivery. Although the analysis is situated in the Welsh context, the paper contributes to a broader understanding of the administrative bottlenecks that can arise when implementing public services in a minoritised language context. It highlights the need to critically examine the institutional dynamics that shape the translation of policy into practice and the implications for minoritised languages such as Welsh. , La llengua és un element clau en la prestació d’una atenció sanitària de qualitat, sobretot en contextos en què els usuaris parlen una llengua minoritzada. A Gal·les, el Govern gal·lès ha reconegut la importància de la inclusió lingüística a través d’iniciatives com ara l’estratègia More than just words, que té l’objectiu d’integrar la llengua gal·lesa als serveis de salut i d’assistència social. L’any 2018, la introducció del Reglament núm. 7 sobre la llengua gal·lesa va marcar un avenç normatiu important, ja que va imposar obligacions legals d’oferir serveis en gal·lès als consells de salut. Malgrat aquests avenços a nivell polític, la incorporació de serveis en llengua gal·lesa en l’atenció sanitària continua sent desigual. Alguns informes han posat de manifest l’existència de buits continuats i d’incoherències en la prestació de serveis en gal·lès, cosa que ha suscitat interrogants sobre els reptes pràctics de la seva implementació i l’impacte que té en els usuaris. En aquest article s’analitzen les barreres estructurals i operatives que es troben els agents situats al nivell meso –en concret els consells de salut locals– responsables d’implementar les polítiques lingüístiques nacionals en l’atenció diària. Malgrat que l’anàlisi se situa en el context gal·lès, l’article aporta una visió més àmplia dels colls d’ampolla administratius que poden sorgir a l’hora d’implementar serveis públics en un context de llengües minoritzades. També destaca la necessitat d’analitzar críticament les dinàmiques institucionals que modulen la traducció de les polítiques a la pràctica i les implicacions per a llengües minoritzades com ara el gal·lès. , La lengua es un elemento clave en la prestación de una atención sanitaria de calidad, sobre todo en contextos en que los usuarios hablan una lengua minorizada. En Gales, el Gobierno galés ha reconocido la importancia de la inclusión lingüística a través de iniciativas como la estrategia More than just words, que tiene el objetivo de integrar la lengua galesa en los servicios de salud y de asistencia social. En 2018, la introducción del Reglamento núm. 7 sobre la lengua galesa marcó un avance normativo importante, ya que impuso obligaciones legales de ofrecer servicios en galés en los consejos de salud. A pesar de estos avances a nivel político, la incorporación de servicios en lengua galesa en la atención sanitaria sigue siendo desigual. Algunos informes han puesto de manifiesto la existencia de vacíos continuados e incoherencias en la prestación de servicios en galés, lo que ha suscitado interrogantes sobre los retos prácticos de su implementación y el impacto que tiene en los usuarios. En este artículo se analizan las barreras estructurales y operativas que encuentran los agentes situados al nivel meso –en concreto los consejos de salud locales– responsables de implementar las políticas lingüísticas nacionales en la atención diaria. Aunque el análisis se sitúa en el contexto galés, el artículo aporta una visión más amplia de los cuellos de botella administrativos que pueden surgir a la hora de implementar servicios públicos en un contexto de lenguas minorizadas. También destaca la necesidad de analizar críticamente las dinámicas institucionales que modulan la traducción de las políticas a la práctica y las implicaciones para lenguas minorizadas como el galés.

Rhetoric and reality: A critical review of language policy and legislation governing official minority language use in health and social care in Wales - Prys, Cynog; Hodges, Rhian; Roberts, Gwerfyl Wyn (Linguistic Minorities and Society, 2021)
A concerted attempt is being made by the Welsh Government to revitalize the Welsh language in Wales through language legislation and policy initiatives. This paper explores the political rhetoric and practical reality of these recent legislative developments, as they pertain to the health care sector. It offers a qualitative analysis of written evidence provided by key stakeholders during the consultation process on the new legally-binding requirements of Welsh Language Standards for health care providers in Wales. We argue that these meso-level service providers are critical linchpins within the health care system and that it is at the meso level that full tensions between the macro rhetoric and micro reality occur. This contribution highlights shortcomings and barriers to Welsh language service provision in health care in Wales and recommends the adoption of wide-ranging, holistic approaches to language planning that meet the language needs of patients outlined by the Welsh Government. Keywords: health and social care, language planning, minority language, Welsh, Wales

Implementing the Evidence for Language-appropriate Health Care Systems: The Welsh Context - Roberts, Gwerfyl W.; Burton, Christopher R. (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Like Canada, Wales, UK is a bilingual nation: the Welsh language is an important part of its national identity and legislative framework. This has implications for the delivery of public sector services, particularly in the context of health and social care, where responding to the language needs of service users is fundamental to quality health care provision. Nevertheless, despite the strengthening policy commitment for a whole-system approach towards enhancing Welsh language services, there is a paucity of evidence to guide best practice in organizational planning in health care settings. This commentary outlines the context and significance of bilingual health care provision in Wales and the implications for building and embedding the evidence base. It calls for further work to translate our knowledge and understanding of language-appropriate practice to provide more effective and sensitive health care services; and to close the implementation gap between evidence and practice. Given the relevance of this challenge for health care providers in Canada who plan and deliver services for French-language minorities, this approach has resonance across our research communities. Thus, in our common pursuit to establish integrated knowledge translation research for language-appropriate health care systems, this commentary offers a focus for reflection, discussion and collaborative action. KEY WORDS: Knowledge management; language; minority health; organizational change; Wales

Health providers’ perceptions on language barriers in Catalonia’s public healthcare system - Rubio-Carbonero, Gema; Gil-Bardají, Anna (Revista de Llengua i Dret, 2025)
In this article, we present the results of an exploratory quantitative study on the situation of communication between healthcare staff in the Catalan public system and users with limited competence in the official languages of Catalonia. The study objective is to offer a comprehensive and empirically grounded overview of the current state of intercultural communication in the Catalan public health system, with and without the involvement of third-party mediation, as perceived by healthcare providers. Data were collected through a structured questionnaire administered to professionals engaged in direct patient care across public health centres in Catalonia, yielding a sample of 1 390 respondents. The findings underscore the high frequency and significant impact of language barriers in clinical encounters and highlight notable deficiencies in the resources currently available to address these challenges. , Aquest article presenta els resultats d’un estudi quantitatiu exploratori sobre la situació de la comunicació entre el personal sanitari del sistema públic català i els usuaris que tenen un coneixement limitat de les llengües oficials de Catalunya. L’objectiu de l’estudi és oferir una visió global i amb una base empírica de l’estat actual de la comunicació intercultural en el sistema públic de salut català –tant amb la mediació de tercers com sense– a partir de la percepció que en tenen els professionals sanitaris. Les dades es van recollir mitjançant un qüestionari estructurat administrat a professionals que treballen en l’atenció directa als pacients en centres públics de salut de Catalunya, que va permetre obtenir una mostra de 1.390 participants. Els resultats posen de manifest l’alta freqüència i el fort impacte de les barreres lingüístiques en les interaccions clíniques, així com mancances notables en els recursos disponibles actualment per afrontar aquests reptes. , Este artículo presenta los resultados de un estudio cuantitativo exploratorio sobre la situación de la comunicación entre el personal sanitario del sistema público catalán y los usuarios con un conocimiento limitado de las lenguas oficiales de Cataluña. El objetivo del estudio es ofrecer una visión global y con base empírica del estado actual de la comunicación intercultural en el sistema público de salud catalán –tanto con la mediación de terceros como sin ella– a partir de la percepción de los profesionales sanitarios. Los datos se recogieron mediante un cuestionario estructurado administrado a profesionales que trabajan en la atención directa al paciente en centros públicos de salud de Cataluña, con el que se obtuvo una muestra de 1.390 participantes. Los resultados ponen de manifiesto la elevada frecuencia y el fuerte impacto de las barreras lingüísticas en las interacciones clínicas, así como carencias notables en los recursos disponibles actualmente para afrontar tales desafíos.

The Silence of South African Health Policies on the Language Barrier Between Healthcare Providers and Patients - Sobane, Konosoang; Van Der Merwe, Chanel; Shandu, Balungile (Language Matters, 2020)
The language barrier continues to compromise adequate healthcare delivery in multilingual healthcare systems. This makes language an important issue for the policy agenda in such systems. This article highlights the silence of selected South African health policies on managing the language barrier in healthcare. The analysis establishes that the selected policies make limited provisions, if any, on the language barrier and fail to account for how the language barrier should be addressed in the provision of care. This silence derives from the level of attention that the subject receives in public discourses and national policies. It is therefore recommended that policies become explicit on how the language barrier in healthcare delivery should be addressed, and that effective implementation as well as monitoring and evaluation mechanisms be put in place to facilitate equitable access to healthcare services for all.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Presente, pasado y (sobre todo) futuro de la atención sanitaria en euskera [Present, past and (above all) future of healthcare in Basque] - Zarate Sesma, Jon; Montes, Aitor (Revista de Llengua i Dret, 2025)
Resumen La normalización de la atención sanitaria sería ofrecer una atención integrada basada en la evidencia y centrada en el usuario (paciente), lo que pasa por una atención en el idioma de elección del usuario. Para la consecución de dicha normalización, y teniendo en cuenta la complejidad del sistema sanitario centrado en el usuario, es necesario poner en marcha políticas que apuesten por el impulso de la conciencia lingüística entre los profesionales sanitarios y ofrecer estrategias para asegurar la asistencia sanitaria integral en euskera. Es imprescindible aprobar un nuevo decreto que reemplace el Decreto 67/2003 y que exija como mínimo el nivel C1 en euskera para el ejercicio de la profesión sanitaria. Del mismo modo, habría que registrar el idioma de elección del usuario a través de la oferta activa, impulsar los circuitos sanitarios en euskera (con la identificación de los servicios y profesionales euskaldunes) y poner en marcha la historia clínica en euskera. Resum La normalització de l'atenció sanitària seria oferir una atenció integrada basada en l'evidència i centrada en l'usuari (pacient), la qual cosa passa per una atenció en l'idioma d'elecció de l'usuari. Per a la consecució de l'esmentada normalització, i tenint en compte la complexitat del sistema sanitari centrat en l'usuari, cal posar en marxa polítiques que apostin per l'impuls de la consciència lingüística entre els professionals sanitaris i oferir estratègies per assegurar l'assistència sanitària integral en eusquera. És imprescindible aprovar un nou decret que reemplaci el Decret 67/2003 i que exigeixi com a mínim el nivell C1 d’eusquera per a l'exercici de la professió sanitària. Així mateix, caldria registrar l'idioma d'elecció de l'usuari a través de l'oferta activa, impulsar els circuits sanitaris en eusquera (amb la identificació dels serveis i professionals bascoparlants) i posar en marxa la història clínica en eusquera. Abstract Healthcare normalisation should involve evidence-based and user (patient)-centred integrated care, provided in the user’s language of choice. To achieve this normalisation, and bearing in mind the complexity of the user-centred healthcare system, it is necessary to implement policies that promote language awareness among healthcare professionals and to offer strategies to ensure comprehensive healthcare in Basque. It is essential to pass a new decree to replace Decree 67/2003, requiring a minimum level of C1 in Basque to work as a healthcare professional. The user’s language of choice should also be recorded by the healthcare system, promoting healthcare circuits in Basque (identifying services available in Basque and Basque-speaking professionals) and making medical records available in Basque. Laburpena Osasun-arretaren normalizazioa ebidentzian oinarritutako eta erabiltzailearengan (pazientearengan) zentratutako arreta integratua eskaintzea litzateke, hau da, nahitaez erabiltzailearen aukerako hizkuntzan. Osasun-sistemaren konplexutasunak beharrezkoa egiten du giza kapitalean oinarritutako kultura-aldaketa: hizkuntza-kontzientzia duten langile ekintzaileak. Eztabaida eta paradigma berriak, diskurtso berria, erabiltzailearengan kokatu behar da, eta ez medikuarengan. Etorkizuna, neurri handi batean, osasun-profesionalen artean hizkuntza-kontzientzia sustatzearen aldeko apustua egiten duten politiken mende dago, bai eta osasun-arreta integrala euskaraz bermatzeko estrategiak eskaintzen dituztenen mende ere. Ezinbestekoa da dekretu berri bat onartzea, 67/2003 Dekretua ordeztuko duena eta lanbide sanitarioan jarduteko gutxienez euskarazko C1 maila eskatuko duena. Era berean, erabiltzaileak arretarako aukeratzen duen hizkuntza eskaintza aktiboaren bidez erregistratu beharko litzateke, osasun-zirkuituak euskaraz sustatu beharko lirateke (zerbitzu eta profesional euskaldunak identifikatuta) eta historia klinikoa euskaraz abiarazi beharko litzateke.